When EU Food Safety Standards Change Mid-Voyage: Frustration, Breach and Risk Allocation in Indian Export Contracts - Sharma, Chaitanya; Makhija, Rashi (Trinity Law Review, 2022)
Indian agricultural exports to the European Union operate in a legal environment where contracts are governed by Indian private law but market access depends on EU food-safety rules that may change during transit. This paper examines whether rejection of an Indian export consignment after a post-shipment revision of EU maximum residue limits should be treated as breach of implied conditions under the Sale of Goods Act, 1930 or as frustration under section 56 of the Indian Contract Act, 1872. Using a doctrinal and comparative method, it studies Indian contract and sale law, Regulation (EC) No. 396/2005, English frustration principles and articles 35 and 79 of the CISG. The paper argues for a sequential liability test based on timing, source of non-conformity, foreseeability, contractual risk allocation and evidence. It also proposes model clauses and expert-led arbitration for residue-report conflicts.
Keywords: Cyber Laws; Intellectual Property Laws; Management; development